Identification of Pseudococcus viburni and Pseudococcus longispinus (Hemiptera: Pseudococcidae) in Musa sp. - Palma Jiménez, Melissa (2018)
To establish appropriate taxonomic relationships in studies of mealybugs it is necessary to study the insects by two techniques: morphological and molecular. The aim of this research is to study mealybugs (Hemiptera: Pseudococcidae) from Ecuador and the Philippines, in banana crop (Musa sp.). The morphological technique light microscopy was used, supported by molecular analysis of two genes: ribosomal 18S and cytochrome oxidase I (COXI). Using both analyses it was possible to identify two species: Pseudococcus viburni (Signoret) and Pseudococcus longispinus (Targioni Tozzetti). The present investigation allowed recognition of molecular variants in the two genes. The difference in the evolution patterns of both genes, and the influence of geographical distances were studied to understand their genetic variations.